Produire une cause victimaire dans un espace de post‑conflit : le traitement de la disparition au sein de la communauté turco‑chypriote - Théotime Chabre (Cahiers Balkaniques)
The following paper explains how was created the cause of missing people’s relatives in the Turkish‑Cypriot community. The main entrance of the paper shows the way disappearance is or is not seen as a public issue, a source of activist engagement and a specific grief by different social groups. This work shows how the rhythm of the Turkish‑Cypriot communal politics and the international negotiations on the reunification of the island influence the growth of this cause. We display how the 2004 referendum represents a turning point. Then, we present the work of the different groups engaged in the cause of the missing people’s relatives. The paper relies on a series of semi‑directive interviews with relatives of missing people, members of the Committee for Missing People in Cyprus and members of the non‑governmental organization “Together We Can!”, in Cyprus, between January and March 2016. The data collected have been checked and completed using archives and secondary sources.